الجريدة الرسمية العدد 42 - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء : قرار رقم 2501 لسنة 2024 -- قرار رقم 2502 لسنة 2024 -- قرار رقم 2503 لسنة 2024 -- قرار رقم 3075 لسنة 2024 -- قرار رقم 3076 لسنة 2024 -- قرار رقم 3078 لسنة 2024 --